PENGARUH PRESTASI BELAJAR KELISTRIKAN DAN PRESTASI BELAJAR KEWIRAUSAHAAN TERHADAP MINAT BEKERJA PADA SISWA SMK ISLAM YOGYAKARTA TAHUN AJARAN 2013/2014 - Ahmad Ridwan (Jurnal Taman Vokasi, 2014)
The purpose of the study (1) to determine whether there is a positive influence between electrical learning achievement of the working interest on the studens Automotive Engineering Islamic Vocational School of Yogyakarta Academic Year 2013/2014; (2) to determine whether there is a positive influence between entreprenuerial learning achievement of the working interest on the studens Automotive Engineering Islamic Vocational School of Yogyakarta Academic Year 2013/2014; (3) to determine whether there is a positive influence between electrical learning achievement and entreprenuerial learning achievement of the working interest on the studens automotive engineering Islamic Vocational School of Yogyakarta Academic Year 2013/2014 .This research was conducted at Islamic Vocational School of Yogyakarta Academic Year 2013/2014. The population in this study were all students of class XI Automotive Engineering totaling 30 students and this study used a sampling saturated or study populations so that the entire population were sampled. This research is correlational and ex post facto categorized. Questionnaire data collection techniques and documentation of learning achivement. The validity of the items were obtained from the product moment correlation. About the reliability of the formula obtained by alpha and declared reliable. Before the data were analyzed first tested the prerequisite analysis is normality test, multicollinearity test, and linearity test. Analysis using partial correlation analysis and multiple regression analysis.From the analysis of the results obtained the following results: (1) There is a positive and significant influence between electrical learning achievement (X1) and entreprenuerial learning achievement (X2) together of the working interest (Y) on the studens automotive engineering Islamic Vocational School of Yogyakarta Academic Year 2013/2014; (2) There is a positive and significant influence between electrical learning achievement (X1) of the working interest (Y) on the studens automotive engineering Islamic Vocational School of Yogyakarta Academic Year 2013/2014; (3) is a positive and significant influence between entreprenuerial learning achievement (X2) of the working interest (Y) on the studens automotive engineering Islamic Vocational School of Yogyakarta Academic Year 2013/2014.Â Keywords: Electrical Learning Achievement, Entreprenuerial Learning Achievement,Â The Working Interest.